2007
DOI: 10.2174/138920307779941505
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Diseases and Structure-Toxicity Relationships: Lessons from Prion-Derived Peptides

Abstract: The physiological form of the prion protein is normally expressed in mammalian cell and is highly conserved among species, although its role in cellular function remains elusive. Available evidence suggests that this protein is essential for neuronal integrity in the brain, possibly with a role in copper metabolism and cellular response to oxidative stress. In prion diseases, the benign cellular form of the protein is converted into an insoluble, protease-resistant abnormal scrapie form. This conversion parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Concerning the role played by metal cations in the - isomerisation, we have shown that the use of the α -helix-inducer TFE to force peptides into a conformation close to the helical one that has been found in may lead to conclusions different from those that can be obtained studying metal cation interaction with peptides in buffer solution. To embed our results in the body of data on PrP structure and function, it is worth considering that the three-dimensional architecture of consists of an unstructured leading tail encompassing residues 23–125 and a C-terminus globular domain, in which residues 126–231 are organized in three α -helices and a two-stranded β -sheet [ 55 , 56 ]. Although it is currently believed that the major structural modifications involved in PrP protein misfolding are located in the unstructured N-terminal region, the present work seems to provide further support to evidence accumulated in the literature that the two prion domains play a different role in the prion conversion, stressing that the N-terminal domain is likely the natural target of metal binding; see [ 57 , 58 ] and references cited therein.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the role played by metal cations in the - isomerisation, we have shown that the use of the α -helix-inducer TFE to force peptides into a conformation close to the helical one that has been found in may lead to conclusions different from those that can be obtained studying metal cation interaction with peptides in buffer solution. To embed our results in the body of data on PrP structure and function, it is worth considering that the three-dimensional architecture of consists of an unstructured leading tail encompassing residues 23–125 and a C-terminus globular domain, in which residues 126–231 are organized in three α -helices and a two-stranded β -sheet [ 55 , 56 ]. Although it is currently believed that the major structural modifications involved in PrP protein misfolding are located in the unstructured N-terminal region, the present work seems to provide further support to evidence accumulated in the literature that the two prion domains play a different role in the prion conversion, stressing that the N-terminal domain is likely the natural target of metal binding; see [ 57 , 58 ] and references cited therein.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. (1) highlights important structural features, as well as documented and potential copper binding sites [27-31]. The octarepeat region, with its four histidine containing octapeptide segments is most often the focus of study, however, as noted above, other sites have also been identified as potential copper binding regions.…”
Section: Introduction – Copper and The Prion Proteinmentioning
confidence: 99%
“…In Huntington disease, conformation of huntingtin protein is changed into β-sheet-rich structures that aggregate into potentially toxic oligomeric species and fibril structures ( Smaoui et al, 2016 ). The secondary structure of prion proteins that induce the severe conformational diseases of the brain, Creutzfeldt-Jakob disease and mad cow disease, clearly changes from α-helix to β-sheet-rich ( Ronga et al, 2007 ; Baskakov, 2009 ; Coleman et al, 2009 ). Thus, β-sheet-rich proteins may be key factors in the development of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%